2016
DOI: 10.18378/rvads.v11i3.4062
|View full text |Cite
|
Sign up to set email alerts
|

Obtenção e caracterização da farinha do albedo de maracujá (Passiflora edulis f. Flavicarpa) para uso alimentício

Abstract: <h2>O maracujá é uma fruta abundante no Brasil, que é considerado o maior produtor do mundo. Cerca de 52% do peso total do fruto é composto por casca (albedo e flavedo), que pode ser reutilizada na forma de farinha como uma fonte de nutrientes para a alimentação e enriquecimento de vários produtos alimentares. Assim, o objetivo do presente trabalho foi estudar o processo de fabricação de farinha do albedo de maracujá amarelo (<em>Passiflora edulis f. Flavocarpa</em>), com variações nas temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1
8

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 7 publications
2
9
1
8
Order By: Relevance
“…In relation to the maceration process, the trend was considerably smaller in samples prepared with macerated albedo than in those not macerated, whereas the sample of macerated peel showed slight increase in comparison to that without maceration. Silva et al (2016) obtained values of 1.82, 3.18, 3.63 and 4.62, after drying at 50, 60, 70 and 80 °C. Oliveira et al (2016) obtained a* of 3.60 and 3.78, both higher than those found in the present study.…”
Section: Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…In relation to the maceration process, the trend was considerably smaller in samples prepared with macerated albedo than in those not macerated, whereas the sample of macerated peel showed slight increase in comparison to that without maceration. Silva et al (2016) obtained values of 1.82, 3.18, 3.63 and 4.62, after drying at 50, 60, 70 and 80 °C. Oliveira et al (2016) obtained a* of 3.60 and 3.78, both higher than those found in the present study.…”
Section: Resultsmentioning
confidence: 84%
“…The same can be observed in relation to the type of sample; samples composed of whole peel had lower water activity than those composed of albedo. Silva et al (2016) found water activity values of 0.535, 0.362, 0.266 and 0.245 in flours prepared with macerated albedo of yellow passion fruit dehydrated at temperatures of 50, 60, 70 and 80 °C, respectively. The values obtained at 70 and 80 °C were higher than those of the present study, 0.213 for MA70 and 0.225 for MA80, possibly because these authors did not grind the albedo before drying, causing higher amount of water to be retained.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations